AKTIVITASMARKETING PUBLIC RELATIONS(MPR) DALAM MENINGKATKAN PELANGGAN - Sulastri, Fitri; Saleh, Gunawan (LPPM Abdurrab Pekanbaru, 2017)
Business competition in the field of hospitality services, especially in Pekanbaru increasingly tight and real for all business. With a touch of Marketing Public Relations (MPR), it is expected to be able to establish various activities to increase the hotel occupancy rate and also increase hotel revenues. The thoughts of the Marketing Public Relations (MPR) also seek to build a mutually beneficial relationship between the hotel and its customers. So that can be achieved destination of hotel that is get high visitor number. The role of Marketing Public Relations (MPR) is felt in the hotel management, because the hotel hopes to further improve the orientation in the realization of image development from the hotel. In an effort to win the competition, the hotel conducts internal communications made by itself such as audio journals, video journals, corporate videos and electronic newspapers for information dissemination. The hotel also conducts external communications involving outsiders such as guests, and media such as journalists. Publication is one of the chosen ways to reach external parties. Publication is defined as a medium that supports Marketing activities to disseminate information to the public. Preaching through media publications is generally done by holding press releases or newscasts and interviews. This study aims to find out the Activity Marketing Public Relations (MPR) in increasing the number of customers on The Baliview Luxury Villas Pekanbaru. Informants in this study is the Marketing Public Relations (MPR) which amounted to 4 Persons. The technique used to determine the informants in this study is purposive sampling, which usually prefers data depth rather than for generalizable representative purposes. The data analysis technique used in this research is qualitative data that can be in the form of words, sentences or narrations, whether obtained from the interview, observation and documentation. Based on the results of research in the field, there are 7 Activities used Marketing Public Relations (MPR) The Baliview Luxury Villas in increasing the number of customers by doing publicity activities, media identity, events, speeches, news, social activities and sponsorship.